Effect of sintering atmosphere on the microstructure and properties of nano-WC modified copper-iron-based oil-containing bearing. (November 2020) - Li, Dongyu; Li, Xiaoqiang; Li, Jingmao; Qu, Shengguan
Abstract: Nano-WC modified copper-iron-based oil bearing was prepared by powder metallurgy. The effect of sintering atmosphere on the microstructure, crushing strength, hardness and oil content of the oil bearing were studied. The results show that under the sintering condition of 865 °C×30min, when the sintering atmosphere is 100%N2, the sintering process stays in the early stage of sintering neck growth, there are a large number of irregular pores in the microstructure. The sintering densification is insufficient, and the sample is in the state of undersintering. When the sintering atmosphere is 100%H2, the dezincification of matrix phase α(Cu) is serious, and there are many long strip microcracks between metal particles. The effective connection between α(Cu) and Fe phase is cut off, so the density of sample is very low. When the sintering atmosphere is 75%H2 +25%N2, α(Cu) forms a united whole through sufficient sintering diffusion bonding, and encapsulates the Fe-rich phase. The sintering densification is very sufficient, the pores in the microstructure tend to be circular. The sintered samples have good comprehensive properties, the density and oil content are 6.60 g/cm 3 and 18.21vol.%, the crushing strength and hardness are 235.81 MPa and 42.41 HB, respectively, showing the best sintering state.